ANALISA KERUSAKAN PENGAIT PEGAS LARAS PISTOL P1 PINDAD - Oktosatrio, Suhendro; Sugihandoko; Tjandra Kusuma, Taufan (PPM Sdirjianbang Akademi Militer, 2024)
While the goals and objectives of the study to analyze the physical properties and mechanical properties of the P1 Pindad Pistol barrel spring hook material because the barrel spring hook is a very important part of the barrel, especially the gun. If the spring hook of this barrel becomes or breaks then the development process will not be such that the project will not go according to the plan of the barrel.From the results of the tests that have been carried out both the test and the test the final result cannot be concluded that the results of the test are the result of the process.easily damaged or brittle clean, but from the results of micro trials produced a lot of mistakes, because in the process of heat treatment of the barrel is not to form a bainit structure that makes steel strong resistance to pressure.Suggestions from the author for the manufacture of the barrel forward so that in the process of special heat treatment when cooling is attempted to form bainit which makes the barrel becomes ductile and not easily broken or damaged.